Electron beam based additive manufacturing of Fe3Al based iron aluminides – Processing window, microstructure and properties - Adler, Lucas; Fu, Zongwen; Körner, Carolin (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2020)
Iron aluminide alloy Fe–28Al–5Ti-1.3B (at.%) based on Fe3Al-phase is processed via Selective Electron Beam Melting (SEBM). After SEBM, iron aluminide parts with a relative density >99.5% are fabricated. Process windows, oxidation resistance, evaporation of aluminum during SEBM and the distribution of Al in the fabricated specimens are discussed. Owing to the presence of TiB2 precipitates, a fine-grained microstructure with Fe3Al matrix is observed. The SEBM-processed as built iron aluminide alloy shows equiaxed grains without a dependency on build direction. Thus, isotropic mechanical properties of SEBM-produced iron aluminide parts are detected. Compared to cast reference samples, SEBM-processed samples without post heat treatment exhibit a higher yield strength.
CRIS-Team Scopus Importer:2020-04-24
Keywords: Additive manufacturing; Iron aluminides; SEBM; Selective electron beam melting